Finansowe i pozafinansowe formy wspierania ochrony środowiska - Zawojska, Aldona; Siudek, Tomasz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2000)
The paper highlights financial and other aspects of environment protection supporting with special focus on Poland's experience. In the European Union it was with the Single European Act, that the environment found its place in the Treaty. The Maastricht Treaty clearly states that the environment becomes community policy. The main principles of environmental action include: prevention, correction at source, "polluter pays" principle polluter has to pay expenses incurred through the prevention) and subsidiarity principle (the actions of the EU have to be limited to measures justifying action at Community level). The Treaty stresses the need for combining free-trade objectives with a high level of environmental protection. It is thus accepted that natural resources constitute the basis and the limits of economic development. The environment is one of the fundamental axes of relations between the EU and the countries of Central and Eastern Europe (CEECs). Some of these countries which are candidates for accession (including Poland) will have to adopt environmental Acquis. In the environmental field, Poland has made some progress since 1989 but major investments are needed. Several types of financial instruments have been specifically created for the implementation of ecological projects. The main sources of their financing cover ecological funds, foundations, commercial banks, leasing institutions and investment funds. Environmental protection has formed an integral part of the PHARE programme of assistance in the economic reform of the CEECs since its launch in 1990. Funds' allocation makes it possible to provide capital for training operations; projects combining environmental protection and rural development; measures accompanying the agricultural policy (ex. introducing organic farming). They also encourage setting up rural development network (promoting waste management, watercourse management, development of renewable energy sources, creation of water distribution networks, development of renewable energy sources, etc.).